A taxonomic revision of the genus Bacopa (Gratioleae, Plantaginaceae) in Argentina - Sosa, María De Las Mercedes; Moroni, Pablo; O’leary, Nataly (Phytotaxa, 2018)
In the present work a revision of Bacopa for Argentina is presented. In this country the genus is integrated by twelve native taxa: eleven species and one variety. Full descriptions, along with distribution information, nomenclatural and taxonomical remarks and illustrations are provided. Two new synonyms are proposed, lectotypes are designated for the species and variety names: Bacopa congesta (second-step lectotype), B. congesta var. hirsuta, B. dubia, B. hassleriana, B. pedersenii, B. ranaria var. guaranitica, B. simulans, Bramia indica, Gratiola repens, Herpestis salzmannii, Herpestis tweedii (second-step lectotype), and a neotype is designated for Monniera rotundifolia.